Infertility - causes, diagnosis, preventive measures and methods of treatment - Mazurek, Aleksandra; Machaj, Damian; Polak, Jakub; Grobecki, Daniel; Lis, Jakub; Machaj, Dominik; Raczkiewicz, Przemysław; Adamik, Weronika (Journal of Education, Health and Sport, 2023)
The problem of infertility affects approximately 20% of married couples, and the number of people affected by this problem is still increasing[5,6]. Developed countries are characterized by the prevalence of primary infertility, while in developing countries there is a high rate of secondary infertility[8,9]. The most common cause of marital infertility is obstruction of the fallopian tubes, which occurs in 30-35% of women and requires surgical intervention. However, both sexes are dominated by immunological and hormonal disorders (25%-30% of cases)[3,4]. The basic examination in which male fertility is determined is the semen analysis, while in women, many tests should be performed in order to make a diagnosis: anamnesis, gynecological examination, ultrasound performed repeatedly during the menstrual cycle (ovulation assessment), hormonal and immunological tests, post-coital tests, bacteriological cultures, hysterosalpingography or laparoscopy [20]. In vitro fertilization is the most effective of all methods of infertility treatment. In vitro fertilization can be performed using the classical method by adding prepared sperm to the egg cells or by microinjection of the sperm into the egg cell[21].